Business Process Reengineering Sistem Laporan Harian Kru Jalan Pada PO.Pelita Mas - Rohman, Moh. Ainur Bahtiar; Suharso, Wildan; Wahyuni, Evi Dwi (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2024)
Every company that has employees who sare not gathered in one place must want speed and efficiency for good information exchange. To elevate quality of company management, it is essential to understand the shortcomings of the employees management. Pelita Mas Otobus Company is a bus company based in Malang City, East Java, which conducts its management system still running conventionally. This has shortcomings in terms of efficiency and accuracy of data on information exchange between employees. From the existing issue, it is important to redesign the business processes at Pelita Mas Bus Company by applying BPR (Business Process Reengineering). BPR is a strategy aimed at redesigning deficient business processes to improve their efficiency. The research begins with data collection, involving observations, process identification, case studies, interviews with Pelita Mas Bus Company, and relevant literature review. Mapping a business process using the ASME (American Society of Mechanical Engineers) standard process map. Utilizing the ASME standard process map, the business process performance is assessed through the throughput efficiency test. Subsequently, the focus shifts towards enhancing and refining the business process redesign to make it more efficient. The ultimate outcome of this study is the redesign of the business process